Survey Study of the Global Disorder Anemia - Raval, Dhriti K.; Patel, Janvi; Pavagadhi, Nidhi; Patel, Himaxi; Trivedi, Naitik; Trivedi, Upama (Asian Journal of Pharmaceutical Research and Development, 2022)
Anemia is caused due to nutritional deficiency and has affected public health at a global level. It has affected both developing and developed countries with majority consequences to human health and social and economic development. According to WHO reports, one-third of the global population (over 2 billion) are anemic due to an imbalance in their nutritious food intake. The main objective behind conducting this survey study was to check the effect of RO versus Tap water drinking on anemia. Through this survey, we found out the side effects, causes of illness, medication effects, and the age groups acquainted with getting anemia. The study was conducted in a region of the Anand district. Total 40 anemic people we had selected randomly for the survey. Out of 40 selected people, 10 were male while 30 were females. We found out in our study that among the 10 male participants, 8 were consuming RO water while 2 of them were consuming tap/simple water, and out of a total of 30 females, 16 of them consuming RO water and 14 are consuming the tap/simple water. In our study, we observed that the age group between 19-25 was most affected by anemic conditions. Out of 10 anemic males, none of them had illnesses. Out of 30 anemic females, three females had another kind of illness. Further in our study, out of 8 males, there were only 2 of them who were found to be vegetarian and non-vegetarian respectively, looking towards female’s ratio out of 27 and 3 females were found to be vegetarian and non-vegetarian respectively. Based on this survey study we can conclude that maximum cases of anemia have been reported between an age group of 19-25 out of the survey of 40 people, of which 10 are males and 30 females. There were 8 males out of 10 who were vegetarian and twenty-seven females out of which 30 were vegetarian and hence could be a possible cause for the prevalence of anemia, another possible cause could be the replacement of simple water with tap water which was found to be a preference of 8 out of total 24 RO consumers,10 males and 14 females may be a cause of anemia.